ACTUALIZATION OF HISTORICAL EMPATHY TO ACHIEVE THE STUDENT PROFILE OF PANCASILA - Susanto, Heri; Sariyatun; Djono (Paedagogia: Jurnal Pendidikan, 2023)
Historical empathy is an aspect that is relevant to the student profile of Pancasila. The achievement of historical empathy can be a way to achieve a student profile of Pancasila. This study aims to: 1) analyze the correlation of students' historical empathy preferences with elements of the student profile of Pancasila; 2) formulate a historical empathy actualization model to achieve a student profile of Pancasila by referring to students' cognitive and affective preferences in learning history. This study uses a quantitative method to determine the correlation of historical empathy with elements of the student profile of Pancasila and a qualitative method to formulate interrelationships between components in the study and formulate a historical empathy actualization model to achieve a student profile of Pancasila. The results showed: 1) there was a significant correlation in the three aspects of empathy with the elements and sub-elements of the student profile of Pancasila; 2) based on students' cognitive and affective preferences in history learning, an actualization model can be formulated using two models, namely actualization that is relevant is the use of edutainment in history learning and project learning based on learning products.